2014
DOI: 10.1149/2.0571412jes
|View full text |Cite
|
Sign up to set email alerts
|

Local Hydrogen Fluxes Correlated to Microstructural Features of a Corroding Sand Cast AM50 Magnesium Alloy

Abstract: Successful in situ spatiotemporal tracking of corrosion processes occurring at heterogeneous Mg alloy microstructures was achieved through tandem analyses involving electron and electrochemical microscopies. Through cross-correlation of scanning electron microscopy and scanning electrochemical microscopy images and subsequent analytical transmission electron microscopy, the morphology and chemical composition of microstructural components on the surface of a sand-cast AM50 Mg alloy were related to their respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…On corroded Mg alloys, some Al‐Mn intermetallic particles have been observed to collect a dome of deposited corrosion product while others remain exposed, a trait also observed on supposed cathodic sites on other Mg alloys . Based on scanning electrochemical microscopy (SECM) measurements, it was suggested that deposition of corrosion products occurred on cathodically active sites with microscopic evidence of corrosion product accumulation at these sites. Recently, we suggested that these corrosion product deposits on Al‐Mn intermetallic particles (Al 8 Mn 5 (Al 1.6 Mn)) in the AM50 alloy are a result of their cathodic behaviour when microgalvanically‐coupled to the α‐Mg matrix 20 , with the cathodic reaction being the reduction of H 2 O to H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…On corroded Mg alloys, some Al‐Mn intermetallic particles have been observed to collect a dome of deposited corrosion product while others remain exposed, a trait also observed on supposed cathodic sites on other Mg alloys . Based on scanning electrochemical microscopy (SECM) measurements, it was suggested that deposition of corrosion products occurred on cathodically active sites with microscopic evidence of corrosion product accumulation at these sites. Recently, we suggested that these corrosion product deposits on Al‐Mn intermetallic particles (Al 8 Mn 5 (Al 1.6 Mn)) in the AM50 alloy are a result of their cathodic behaviour when microgalvanically‐coupled to the α‐Mg matrix 20 , with the cathodic reaction being the reduction of H 2 O to H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…10 Therefore, improving the corrosion resistance of magnesium and its alloys is an interesting subject of studies with a goal of attaining the required corrosion resistance and a reduced hydrogenevolution rate, which are key for biomedical applications. 5 Many investigations have focused on improving the corrosion resistance of magnesium alloys via using surface treatments, [11][12] controlling orientation, 13,14 controlling microstructure, [15][16][17] and using alloying elements. [18][19][20][21][22][23][24][25] Among these methods, the use of alloying elements in a solid solution strongly influences the corrosive and mechanical properties of magnesium alloys.…”
mentioning
confidence: 99%
“…(reaction 1). H22H++2e The local flux of H 2 gas from the surfaces of metal alloys has been investigated by SECM in the SG/TC mode …”
Section: Methodsmentioning
confidence: 99%